Manajemen Resiko Proyek Pengembangan Perangkat Lunak Berbasis Open/Free Source dengan Menggunakan Metode AS/NZS 4360 dan Analytical Hierarchy Process (AHP) - Rasyidi, Lili; Wahyuningsih, Utami; Chairat, Arief Suardi Nur; Abiyyu, Dejan (PETIR, 2024)
The increasing needs of information and communication technology affects the emerge of information and communication technology projects. One type of its project is software application development project, which this kind of project often totally or partially fails. Indonesia, as one of developing country requires various software types for their business environment in all aspects such as government, private sector or also personal use. The high use of information technology was not followed by awareness and financial ability to use proprietary technology, which is costly and monopolized by some certain vendor. The needs of uncostly and monopolized software was responsed by a software development community and some software vendor which later produced some softwares that are free to use and developed. These kind of softwares are called free and open source software (FOSS). Open source technology that emerged and boomed since few years lately still have various weakness and need to be accomodated by software developers and consumers. Differ from proprietary software, product support from vendor or community isn’t always available. This research’s aim is to identify, structuring and also analyze risk factors of open source-based software development.First stage of this research is to identify risk factors based on Carr et al, (1993) an approach named taxonomy-based risk identification. Combinined with risk identification by Peer, (2006) and FFIEC, (2004), it resulted new factor atribute. Second stage of research is risk assessment of identified risk factors. Most of risk assessment influenced by perception from expert, therefore, the assessment methods is needed to accomodated expert perception. This research used two perception-based methods, qualitative assessment by AS/NZS 4360, (1999) and Analytical Hierarchy Process proposed by Saaty, (1996). Both of this methods was assumed able to map expert’s perception and yield classification and priorities of risk factors.As a conclusion, risk factors identification by Carr et al, (1993) need to be enhanced by new atribute, which is the license options. This atribute becomes an important matter in course of software development because it can influence project succes and software legal attitude. AS/NZS 4360 Qualitative risk assessment classifies risk factors into three classification: extreme, high and moderate (while the low classification isn’t present). AHP risk assesment yields risk factors priority and classification by converting risk weight into four classification : extreme, high, moderate and low. Keywords : Risk Assessment, Taxonomy Software Development, Qualitative Analysis, Pairwise Comparison, analytical Hierarchy Process.